2020
DOI: 10.1093/infdis/jiaa277
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Triphosphate Neutralizes Pneumolysin-Induced Neutrophil Activation

Abstract: Background In tissue infections, adenosine triphosphate (ATP) is released into extracellular space and contributes to purinergic chemotaxis. Neutrophils are important players in bacterial clearance and are recruited to the site of tissue infections. Pneumococcal infections can lead to uncontrolled hyperinflammation of the tissue along with substantial tissue damage through excessive neutrophil activation and uncontrolled granule release. We aimed to investigate the role of ATP in neutrophil r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…CD11b regulates leukocyte adhesion and migration to mediate inflammatory responses, while CD62L is an adhesion molecule that mediates neutrophil rolling and sheds upon neutrophil activation. In addition, and consistent with previous studies [ 57 , 58 , 59 , 60 ], we observed that PLY caused an increased release of elastase, suggestive of degranulation and enhanced ROS production ( Figure 1 C,D). A recent study demonstrated that PLY activates NET formation [ 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…CD11b regulates leukocyte adhesion and migration to mediate inflammatory responses, while CD62L is an adhesion molecule that mediates neutrophil rolling and sheds upon neutrophil activation. In addition, and consistent with previous studies [ 57 , 58 , 59 , 60 ], we observed that PLY caused an increased release of elastase, suggestive of degranulation and enhanced ROS production ( Figure 1 C,D). A recent study demonstrated that PLY activates NET formation [ 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…13 Briefly, we incubated washed human platelets in Tyrode buffer containing Ca 21 and Mg 21 with phosphate-buffered saline (PBS), 20 mM thrombin receptor activator peptide 6 (TRAP-6), pneumolysin, or pneumococci (D39, TIGR4, or their pneumolysin-free mutants D39Dply and TIGR4Dply). 14,15 We did grow bacteria to the mid-log exponential phase before incubating 1.8 3 10 6 bacteria with 9 3 10 6 platelets (ratio bacteria platelets 1:5) for 2 or 3 hours. We incubated platelets with pneumolysin at different concentrations or the pneumolysin mutants for 10 minutes.…”
Section: Flow Cytometry-based Platelet-activation Assaymentioning
confidence: 99%
“…To test the cytolytic activity of pneumolysin proteins, the hemolysis assay was performed as described recently. 15 In a subset of experiments, a pneumolysin-inhibiting monoclonal mouse antibody (7.5 mg/mL), polyclonal rabbit anti-pneumolysin antibodies (10 mg/mL), or a pharmaceutical human IgG preparation (1 mg/mL; IgG-enriched Privigen; CSL-Behring) were added.…”
Section: Hemolysis Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, initial mild manifestations may result in severe invasive diseases such as pneumonia, meningitis, and sepsis [2, 3]. One of the most important and well-studied secreted virulence factors of pneumococci is the pore-forming cytolysin pneumolysin (Ply) [4]. Moreover, pneumococci secrete high amounts of hydrogen peroxide (H 2 O 2 ) as a product of the pneumococcal carbohydrate-metabolizing enzyme pyruvate oxidase SpxB [5].…”
Section: Introductionmentioning
confidence: 99%